(untitled) (Revista BOEM, 2024)
Digital media are gradually making their presence felt in people’s lives, with text messages, images, audio and videos being used frequently. In this scenario, digital videos have a unique place, as they present audiovisual stimuli that foster communication and encourage greater interest among those who watch them. The aim of this study is to analyze the aspects of video production by Vocational and Technological Education students that contribute to the teaching and learning process in the subject of Probability. This is a qualitative study of na applied nature and its procedures are based on the theoretical assumptions of Thiollent (2022). The research was carried out by students from a third-year secondary school integrated into the technical área of a technical located in the city of São Paulo. Ten videos were produced, and, after analysis, the results indicate that, in addition to the skills required to make appropriate use of digital technologies, the production of digital videos demands authorship on the part of the students, requires research and participatory action in their teaching and learning process